2015
DOI: 10.14260/jemds/2015/1796
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial and Orbital Injuries Evaluation by Three Dimensional MDCT

Abstract: There has been considerable increase in maxillofacial and orbital injuries due to road traffic accidents, falls and assaults. There is need for accurate detection of these maxillofacial bony fractures. MDCT is the method of choice in the evaluation of maxillofacial traumas, as it allows accurate determination of the presence, location and extent of fractures especially in cases of communited fractures, rotational deformities and multiple bone fractures also having advantage to diagnose even in patients with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…The total number of fractures recorded were 102. By far the commonest fracture on CT was maxillary sinus wall fracture (20.65%) followed by followed by orbital floor fractures (16.6%), nasal fractures (14.7% ), mandibular fractures (11.7% ), tripod fractures (8.8%), isolated zygomatic arch fractures (7.8%), Le Fort fractures (6.8%), orbital wall fractures (4.9%), NOE complex fractures (2.9%), dento-alveolar fractures of maxilla (1.9%) and other fractures (2.9% ) which was similar to study done by Gabriela Tomlich et al [13], Kaleem Ahmad et al [7], Shrisail Patil et al [14].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The total number of fractures recorded were 102. By far the commonest fracture on CT was maxillary sinus wall fracture (20.65%) followed by followed by orbital floor fractures (16.6%), nasal fractures (14.7% ), mandibular fractures (11.7% ), tripod fractures (8.8%), isolated zygomatic arch fractures (7.8%), Le Fort fractures (6.8%), orbital wall fractures (4.9%), NOE complex fractures (2.9%), dento-alveolar fractures of maxilla (1.9%) and other fractures (2.9% ) which was similar to study done by Gabriela Tomlich et al [13], Kaleem Ahmad et al [7], Shrisail Patil et al [14].…”
Section: Discussionsupporting
confidence: 86%
“…Motorbike is one of the major source of transport in Nepal as Nepal is low income country and its easy to travel with motorbike in hilly areas. Out of 22 patients involved in RTA, alcohol by any means was found to be involving in 12 patients (54.54%) which is in accordance with study conducted by V. Ravindran et al [12], Gabriela Tomlich et al [13], Shrisail Patil et al [14], Subhasraj K et al [15], Rajib khadka et al [10].…”
Section: Discussionsupporting
confidence: 84%
“…Zygomaticomaxillary fractures were also quite common in their study (14%); whereas in our study, nasal bone fractures were the second-most common. Similarly, Patil et al also found the nasal bone to be the most common bone to be fractured, followed closely by naso-ethmoidal and zygomatic-maxillary complex fractures [13]. Axial and coronal images were found to be better for fractures of orbit fractures.…”
Section: Discussionmentioning
confidence: 89%